2022
DOI: 10.1080/19336934.2022.2149209
|View full text |Cite
|
Sign up to set email alerts
|

A screen of small molecule and genetic modulators of life span in female Drosophila identifies etomoxir, RH5849 and unanticipated temperature effects

Abstract: Mifepristone increases life span in female Drosophila melanogaster , and its molecular target(s) remain unclear. Here small molecule and genetic interventions were tested for ability to mimic mifepristone, or to decrease life span in a way that can be rescued by mifepristone. Etomoxir inhibits lipid metabolism, and significantly increased life span in virgin and mated females, but not males, at 50 µM concentration. Pioglitazone is reported to activate both mammalian PPARγ and its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 55 publications
1
7
0
Order By: Relevance
“…This difference may be due to the more intensive mating protocol employed here, where newly-eclosed females were mated to young, mature w[1118] strain males for 48 hours. Consistent with this conclusion, our previous studies indicated that 48 hours mating reduced female life span to a greater extent than did 24 hours mating [ 39 ], and that the more intensive mating protocol yields shorter mated female life spans and greater increases in life span upon mifepristone treatment [ 19 ].…”
Section: Discussionsupporting
confidence: 64%
See 4 more Smart Citations
“…This difference may be due to the more intensive mating protocol employed here, where newly-eclosed females were mated to young, mature w[1118] strain males for 48 hours. Consistent with this conclusion, our previous studies indicated that 48 hours mating reduced female life span to a greater extent than did 24 hours mating [ 39 ], and that the more intensive mating protocol yields shorter mated female life spans and greater increases in life span upon mifepristone treatment [ 19 ].…”
Section: Discussionsupporting
confidence: 64%
“…Midgut diameter was assayed in flies at 14 days of age, which corresponds to 12 days of treatment +/- mifepristone. This time point was selected because this is the age where life span curves of mated females treated +/- mifepristone typically begin to diverge, and this time point has previously been found to show robust mating-induced midgut hypertrophy that is reversed by mifepristone treatment [ 21 , 39 ]. In the w[1118] control strain, mating caused increased midgut diameter, and this was significantly decreased by mifepristone treatment, consistent with previous assays of the w[1118] strain and other strains [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations